Endophytic Bacillus species isolated from mangrove plants, and their antagonestic effects against some pathogenic bacterial strains - Ibrahim MS Eldeen,; LSM Alejandra,; J Saidin,; NAM Zin, (International Journal of Phytomedicine, 2015)
This study aimed to isolate bacterial endophytes with potential antimicrobial effects from five mangrove plants and to investigate the stability of the most active metabolites under different PH and temperature. Bacterial colonies were isolated from the collected plant parts. Bacterial strains with potential antagonistic interactions were subjected to idnetification by VITEK 2 system or sequencing of the 16S rRNA. MIC values of the crude substances were determined against Bacillus cereus, Streptococcus uberis, Escherichia coli, Klebsiella pneumonia and Salmonella typhiumurium using the the serial dilution technique.The stability of the most active crude extracts was examined under different, PH (2-7) and temperature (60 -90 °C). Twenty one of the isolated strains showed potential antagonistic effects. Of these, 16 identified as Bacillus species. Best antimicrobial effects were recorded for Bacillus tequilensis against, B. cereus and S. typhimurium (MIC value=65 µl/m1), S.uberis (MIC value 78 µl/ml), E.coli and K.pneumonia (MIC value=125 µl/m1). Both Bacillus subtilis and Brevibacillus brevis inhibited growth of S. typhimurium with MIC value of 78 and 60 µl/m1 respectively. The metabolites of B.subtilis and B.tequilensis appeared to be stable under PH2-9. Product of B.subtilis showed stability under high temperature (90 °C) against S. typhimurium. The isolated endophytes possessed wide range of antimicrobial activities against the selected pathogens. Bacillus tequilensis and B.subtilis produced the most active metabolites. This is the first report on isolation of endophytic strains of B.tequilensis. The crude extracts obtained from B.tequilensis and B.subtilis in this study could be further developed as food preservatives.